Sexual development and gonads function in children and adolescents after allogeneic stem cell transplantation using different conditioning regimes - L. I. Papusha; D. N. Balashov; A. N. Tul'pakov; E. V. Skorobogatova; E. E. Kurnikova; Y. V. Skvortsova; A. A. Maschan (Онкогематология, 2022)
Various conditioning regimes influence on sexual development and gonads function in children and adolescent after stem cell transplantation was studied. 45 patients were enrolled in the study: 23 patients with aplastic anemia (АА), who received non-myeloablative conditioning, and 22 patients with acute myeloid leukemia (AML) after myeloablative conditioning. Sexual development was estimated by Tanner classification, laboratory tests included gonadotropic hormones, sex steroids, antiMullerian hormone and inhibin B level detection. It has been shown that non-myeloablative conditioning does not influence sexual development in any patients. Extremely high frequency of gonads lesion in patients received myeloablative conditioning was registered: hypergonadotrophic hypogonadism in 8 from 12 girls with severe decrease of ovaries functional reserve in all patients; germinal epithelium lesion in 9 from 10 boys.